Firefighter tenability and its influence on wildfire suppression. (June 2019) - Penney, G.; Habibi, D.; Cattani, M.
Abstract: This paper provides analysis of international fire service siege wildfire suppression thresholds and reports on the effect of forest fuel structure, fire weather condition and terrain on the suitability of suppression strategies. Further, this study applies a fire engineering approach whereby siege wildfire behaviour is deterministically assessed against firefighter tenability thresholds. This research is significant as it is the first study to consider human tenability as a factor in determining appropriateness of wildfire suppression strategies and tactics. The results clearly demonstrate offensive siege wildfire suppression involving direct head fire attacks by personnel and appliances exposes firefighters to untenable conditions well in advance of the head fire edge. Accordingly fire services may need to consider earlier instigation of defensive strategies and increased reliance on aerial wildfire suppression. Highlights: Wildfire dead man zone is significantly greater than current literature reports. Firefighter tenability should be considered when setting suppression strategies. Wildfire fuel geometry plays a significant role in head fire intensity.